Монгол орны эрдэст нууруудын литий, ураны судалгаа - С, Ариунбилэг (Proceedings of the Mongolian Academy of Sciences, 2017)
No Mongolian Abstract For the last 30 years Central Asian and other countries closed salted lakes containing Li, U and other rare elements ( B, Br. J) are explored and used as an energy resources. Thus, it is important to study and practice our country’ salt lakes which contains Li, U and other elements.